Uji Ekstrak Ethanol 70% Daun Kembang Bulan (Tithonia Diversifolia A. Gray) terhadap Efek Diuresis pada Tikus Putih Jantan Galur Wistar (Rattus Norvegicus) - Satria, Muhammad Tangguh; , dr. Devi Usdiana Rosyidah, M.Sc (2017)
Background : Hypertension is a condition when the blood pressure in the blood vessels chronically elevated. Data from the National Health and Nutrition Examination Survey (NHNES) since 1999-2000, the incidence of hypertension for adults is about 29-31%. the prevalence of hypertension in Indonesia was 26.5 percent. Now it is known as 5 groups of first-line drugs (first-line drug) that is commonly used for initial treatment of hypertension, one of diuretic which is diuretic drugs are made from chemicals that can cause many side effects, hence the need for an effort to minimize side effects through the use of herbs. Objective : To determine the diuresis effect of Kembang Bulan leaf (Tithonia diversifolia A.gray) extract on white male rats strain wistar (Rattus norvegicus). Kembang bulan leafe contain flavonoid group of flavonol that can causing diuresis effect by incresing natriuresis and klouresus mechanism. Method : The research is laboratory experimental using post test only control group design method. The research subjects are 30 white male rats (Rattus norvegicus) Strain wistar, the ages are around 2-3 mounths, weigh abaut 150-250 grams, devided to 5 groups. Group 1 was given 2ml/200grBW of aquades, group 2 was given 0,45 mg/200 grBW dosage in 2 ml solution of hidrochlortiazid, grup 3 was given kembang bulan leaf ekstract dosage I (0,6 gr/200 mgBw in 2 ml solution), grup 4 was given kembang bulan leaf ekstract dosage II (1,2 gr/200 mgBw in 2 ml solution), and grup 5 was given kembang bulan leaf ekstract dosage III (2,4 gr/200 mgBw in 2 ml solution), rat urine's volume containment and measurement have to be done every 6 hours per day during observetion. Result : Stastitical calculating using Kruskal-Wallis shows significant differences of urine volume (p<0,05)n between treatment group. Conclusion : The summary of the research is showing Kembang Bulan leaves exstract dosage I and II have diuresis effect then dosage III has diuresis effect that par with hidrochlortiazid. Keyword : Extract, kembang bulan leaf (Tithonia diversifolia A.gray), diuresys